Designing trustful and empowering human-robot interactions using a living lab approach - Vallee, R.; Auberge, V. (Gerontechnology, 2024)
he notion of trust, not yet enough scientifically defined, that a machine can inspire explicitly or implicitlyhas been much studied (Schaefer et al., 2016; Chang & Joseph, 2020). For fragile users in isolated situations, it hasbeen shown that by manipulating very simple robot parameters, it is possible to trigger strong attachment anddesirability of the machine (Aubergé et al., 2014). Two research questions arise: 1) What are the robot parametersthat develop this trust? 2) Does this trust have beneficial or adverse consequences for these users and the entireecosystem that cares for them? In this presentation, we address the first question using a living lab approach (Pinoet al., 2013). Methods and Materials: For our research, we used the first drawings and prototypes of the newMiroki robot currently under development. This robot is both a social and a logistical robot, serving careprofessionals as well as patients and their caregivers. Over the past 2 years, we have carried out the followingstudies in hospitals and nursing homes: 1) Three workshops with 15 older adults and 6 semi-directive interviewswith experts in hospital innovation to gather their initial reactions to this robot and discuss their perception of thebenefits and risks associated with its use. 2) Two workshops with a total of 67 hospital caregivers to betterunderstand the notion of trust they might have in such a robot. 3) An experiment with 30 caregivers in a scenario forhelping older adults to hydrate themselves (a scenario in which we introduced the robot as an object or a subject,varying its degree of expressivity). 4) A study with 48 people (10 older adults, 10 informal caregivers, 14 hospitalcaregivers and 14 other hospital staff) to ensure that the robot's development was guided by users' needs, whilealigning the objectives of the innovation project with the requirements of the geriatric hospital environment. Resultsand discussion: Some of our results confirm the main findings of the scientific literature, in particular concerning 1)the importance of a humanoid / animaloid design as an important factor in this acceptability (Barnes et al., 2017)compared with purely industrial robots, 2) the strong link between the robot's perceived usefulness in its use casesand its level of acceptability (Lee et al., 2018), 3) the link between the quality of the robot's interaction and itsacceptability to its end-users (Whelan et al., 2018). Other results show the influence of parameters little studied sofar on the perception of the robot, such as the influence of introducing the robot as an object (machine) versus asubject as well as its level of expressiveness. Thus, the robot Miroki 1) introduced as a subject (rather than anobject) with a high degree of expressiveness seems to be perceived as more flexible and inspiring more trust 2)with a high degree of expressiveness (rather than a low one) and presented as an object seems to be perceived asmore tender. How these parameters influence user perception over time will require further research. The impact ofthese parameters on user perception and interaction with the robot over time will be addressed in further studies